1996
DOI: 10.1016/0735-1097(96)81240-x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for evaluation of left ventricular diastolic function: Spatial and temporal analysis of left ventricular filling flow propagation by color M-mode doppler echocardiography

Abstract: Spatial and temporal analysis of filling flow propagation by color M-mode Doppler echocardiography was free of pseudonormalization and correlated well with the invasive variables of left ventricular relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
2
10

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(215 citation statements)
references
References 22 publications
9
194
2
10
Order By: Relevance
“…Also, in a univariate analysis, several investigators found a significant correlation between left atrial pressure, left ventricular minimal pressure or left ventricular enddiastolic pressure on one hand and v p on the other hand [47][48][49]52,58,59,61] . In contrast, in multivariate analysis, most studies were not able to demonstrate a significant [47] , in a multivariate model, both the relaxation constant and the difference between left ventricular pressure at mitral valve opening and minimal left ventricular pressure remained simultaneously significant variables for determining v p .…”
Section: Filling Pressurementioning
confidence: 99%
See 3 more Smart Citations
“…Also, in a univariate analysis, several investigators found a significant correlation between left atrial pressure, left ventricular minimal pressure or left ventricular enddiastolic pressure on one hand and v p on the other hand [47][48][49]52,58,59,61] . In contrast, in multivariate analysis, most studies were not able to demonstrate a significant [47] , in a multivariate model, both the relaxation constant and the difference between left ventricular pressure at mitral valve opening and minimal left ventricular pressure remained simultaneously significant variables for determining v p .…”
Section: Filling Pressurementioning
confidence: 99%
“…Takatsuji et al [52] determined the v p using the baseline shift, displaying the flow velocities higher than the aliasing velocities in blue within the red filling flow signals. First the point of maximal velocity around the mitral orifice in early diastole was located.…”
Section: Quantifying V P From a Colour M-mode Doppler Imagementioning
confidence: 99%
See 2 more Smart Citations
“…During myocardial ischemia or HF, there is slowing of the LV base to apical flow propagation 60 , 61 . A Vp > 50 cm/s is considered normal 62 while a value < 45 cm/s in patients > 30 years is consistent with DD 63 .…”
Section: Flow Propagationmentioning
confidence: 99%